EVALUASI DESAIN KEMASAN, POPULARITAS MEREK DAN BUDAYA KONSUMEN TERHADAP CITRA MEREK AQUA - Tafiprios Tafiprios; Rani Arbi (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
This research aimed to analyze the influence of Packaging, Brand Awareness and Consumer Culture to Brand Image. The object of this research is consumer of Aqua in Jakarta. This research was done to 100 respondents by using accidental sampling technique and using the SPSS 22.00 program as a data processing. The result of this research shows that either simultaneouslyor partially, the variable of Packaging, Brand Awareness and Consumer culture influence the Brand Image of Aqua In Jakarta. It has been proven from the result of (f) simoultant test and the result of (t) partial shows significant point of three independent variables that supports the hipothesys. Therefore, the accepted assumption is, there is influence between Packaging, Brand Awareness, and Consumer Culture to Brand Image of Aqua in Jakarta. Keywords: packaging, brand awareness, consumer culture, brand image.